Piezoelectric and ferroelectric properties of KNbO3added Bi0.5Na0.5TiO3ceramics - Puripat Kantha (2018)
© 2017 Trans Tech Publications, Switzerland. The fabrication of lead-free (1-x)Bi 0.5 Na 0.5 TiO 3 - xKNbO 3 or (1-x)BNT-xKN ceramics where x = 0.00, 0.05, 0.10, and 0.15 was carried out by the modified two-step mixed oxide method. The effects of KNbO 3 on structure, piezoelectric and ferroelectric properties were systematically investigated. XRD results revealed that the (1-x)BNT-xKN ceramics with low KN content of x less than 0.05 contained ferroelectric phase with a rhombohedral symmetry while the ceramics with x = 0.05 possessed pseudocubic structure. The higher KN content (x ϵ0.10) ceramics had symmetries rhombohedral structure. At room temperature, the highest Pr and low Ec were obtained when the composition of x = 0.05. Moreover, the results showed the moderate KN addition could enhance the piezoelectric response. The d33 of 0.95BNT-0.05KN reached as high as 125 pC/N.